2000
DOI: 10.1007/pl00008195
|View full text |Cite
|
Sign up to set email alerts
|

Blomstrand osteochondrodysplasia: three novel cases and histological evidence for heterogeneity

Abstract: Blomstrand osteochondrodysplasia (BOCD) is a rare, autosomal recessive, lethal skeletal dysplasia characterized by generalized osteosclerosis and advanced skeletal maturation. The histopathological characteristics of three novel cases (two isolated cases and a sib-pair) of BOCD are presented and correlated with the clinical and radiographical findings, and the relevant literature is reviewed. The results of our study confirm the existence of two separate types of BOCD, which we propose naming type I: the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…35 Histological analysis of the bone-perichondrial ring in Blomstrand fetuses revealed that in contrast to control or FGFR3-mutated fetuses, only cortical/periosteal bone was present and associated with defective bone-perichondrial ring development (personal data). 36 This observation is supported by data obtained in PTHrP and PTHR1 knockout mice 46 -48 and indicates that formation of the bone-perichondrial ring is not similarly affected by FGFR3 and PTHR1 mutations. Further analysis of genetically manipulated mice overexpressing both FGFR3 and PTHR1 genes should help define the specific defects.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…35 Histological analysis of the bone-perichondrial ring in Blomstrand fetuses revealed that in contrast to control or FGFR3-mutated fetuses, only cortical/periosteal bone was present and associated with defective bone-perichondrial ring development (personal data). 36 This observation is supported by data obtained in PTHrP and PTHR1 knockout mice 46 -48 and indicates that formation of the bone-perichondrial ring is not similarly affected by FGFR3 and PTHR1 mutations. Further analysis of genetically manipulated mice overexpressing both FGFR3 and PTHR1 genes should help define the specific defects.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, analysis of endochondral growth plate from fetuses with Blomstrand's lethal chondrodysplasia has shown increased bone collar (cortical bone) thickness and/or thickening of subperiosteal ossification overgrowing the growth plate, but no inward growth of bone-perichondrial ring (personal data). 36 Conversely, although not histologically documented, defective boneperichondrial ring formation in patients with Jansen's metaphyseal chondrodysplasia is strongly suggested by the striking widening of the metaphysis associated with an irregular metaphyseal border on X-ray analysis. 35 Thus, PTHR1 mutations in humans, as FGFR3 mutations, are associated with defective perichondrial bone formation in addition to abnormal endochondral ossification.…”
mentioning
confidence: 99%
“…Loss of PTH1R causes Blomstrand chondrodysplasia, which is characterized by a chondrodysplasia quite similar to what has been FETAL AND NEONATAL MINERAL METABOLISM found in Pth1r null fetal mice (296,489). It is embryonically lethal; therefore, there are no cord blood measurements of calcium, phosphorus, etc.…”
Section: E Human Datamentioning
confidence: 85%
“…These Pthr1-null fetuses are globally smaller than wt and display the Pthrp-null phenotype of accelerated endochondral ossification and dysplasia combined with the Hoxa3-or Pth-null phenotype of significant undermineralization of the skeleton [39]. The human equivalent of absence of the PTH1R, Blomstrand chondrodysplasia, shows similar features [46,47].…”
Section: Role Of Pthrp and Pth In Combinationmentioning
confidence: 80%